DOP075 Colonic gamma delta t-cells respond innately to NKG2D ligands and are grossly dysregulated in active inflammatory bowel disease. (16th January 2018) - Dart, R J; Vantourout, P; Laing, A; Digby-Bell, J; Powell, N; Irving, P; Hayday, A
Abstract: Background: Although gamma delta T cells, are sentinels of epithelial dysregulation, their role in IBD is understudied. The disproportionate intraepithelial enrichment of murine γδ T cells with specific T cell receptors (TCR) is well established, mirroring which we recently described Vγ4Vδ2 - T cells as the signature subset in human colonic epithelium (Di Marco Barros, Cell 2016). Given that these cells express a plethora of innate receptors, they are ideally situated to respond to the altered barrier function preceding the development of IBD. Methods: Colonic biopsies were obtained from controls and patients undergoing colonoscopy. Lymphocytes were isolated using a short-term culture method, and analysed by flow-cytometry. RT-qPCR was performed on whole tissue. FFPE tissue was imaged using RNAscope. Results: The proportion of total T cells expressing the γδ TCR was evidently lower in inflamed tissue vs. healthy controls 5% vs. 8% ( p = 0.05); with significantly fewer gut-resident Vδ2 - cells expressing Vγ2/3/4 chains in patients with active inflammation (54% vs. 78% p = 0.02). Moreover, RNAscope data revealed that many γδ cells were not associated with the colonic epithelium, as is typical in healthy samples. Consistent with this, Vδ2 - cells in inflamed tissues demonstrated altered surface phenotypes, with significant loss of αΕβ7 (CD103) expression (90% vs. 36% p < 0.0001), in concert with downregulation of the natural killer receptor 2B4 and upregulation of CD71, collectively suggesting an activated phenotype. Upon stimulation, Vδ2 - cells demonstrated a "Th1" phenotype, expressing IFNγ and TNFα that was potentiated in donors with active inflammation. By contrast, Vδ2 - cells were not significant sources of IL17A, IL22 or IL13 in our cohorts of either Crohn's disease or colitis. Vδ2 − cells universally expressed NKG2D, an important activating receptor and IBD drug target, and unlike CD8+ TCRαβ cells, made innate cytotoxic responses to NKG2D ligands, without requirement for conscious activation of the TCR. Moreover, the genes encoding NKG2D ligands were substantially upregulated in inflamed mucosa: ULBP2 (8-fold, p < 0.002); MICA (3-fold, p < 0.006). Conclusions: Vδ2 - cells comprise a significant population of T cells in the human colon and given their potential to respond innately, they may be a major player sensing dysregulation in the colonic epithelial compartment. We have demonstrated that this compartment is substantively altered in gut inflammation, with atypical TCR usage; an activated phenotype; and mis-localisation, all of which may reflect responses to upregulated NKG2D ligands. Hence this compartment is particularly pertinent vis-à-vis ongoing clinical trials assessing the efficacy and safety of blocking NKG2D.